Maternal syphilis and complications during pregnancy - Neira Varillas, Milagros Rocío (2019)
Syphilis is a curable infection caused by a bacterium called Treponema pallidum, it is transmitted sexually and also, during pregnancy, from the mother to the fetus; and the absence of treatment in pregnancy leads to adverse outcomes such as late fetal death, prematurity and neonatal death. We describe the natural course of a case of maternal syphilis that occurred with complications during the end of pregnancy and led to neonatal death.